Computational Method and Simulation of Reliability for Series, Parallel, and k-Out-of-n Systems with Interval Parameters. (15th September 2021) - Fang, Yongfeng; Tee, Kong Fah; Cheng, Zhengwei; Yong, Xu
Abstract : For series, parallel, and k -out-of- n voting system reliability calculation methods, the six σ principles have been proposed in this study to derive the interchange relationship between interval parameters and random parameters. The interval reliability index can be expressed in the function of the random reliability index. The interval reliability index can then be transformed into a random reliability index. The computational method of the reliability for series, parallel, and k -out-of- n voting systems with interval parameters is established. Finally, it has been shown that the proposed method is rational, practical, and applicable with two engineering practical simulations.